African Women in Peace Building - Dr. Odike Ebenezer Levi (International Journal on Integrated Education, 2022)
African nations have been ravaged by conflict, resulting in destabilization, displacement, and infrastructural destruction, all of which have gender-specific consequences. The impact of conflict on African women has been severe. In Africa, for example, an estimated 70% of Africa refugees are women and children. This paper examines African women and peace building. It addresses how Africa women have performed important roles as peace negotiators and peace educators in both families and society. However, women today have been relegated to the background in peace building processes, which can in part explain why we have largely failed in this direction. This paper used the historical approach and applied the radical feminism theory to guide the work. The paper identifies women’s needs that must be met to stimulate involvement in peace building and to enact well-informed planning, policymaking, and action to build a culture of peace in Africa. Finally, the paper suggests ideas to integrate a gender perspective into conflict resolution and peace building efforts so that African women’s voices can be heard.